1. 4x + y = 2 x - 4y = 9
ax + by = 8 bx +ay =1
ans : 4x+y =2......(1)
x - 4 y = 9 .......(2)
由第(1) 可得 y = 2 - 4x 代入第二式
x - 4 (2-4x) = 9
x - 8 + 16x = 9 , 17x = 17 , x = 1 , 代入 (1) , 4 +y =2, y = -2
x =1, y = -2, 代入 ax + by = 8, bx +ay =1
a -2b = 8 .....(1)
b - 2a = -1 ......(2)
由(1) 得 a = 8 +2b , 代入第(2)
b - 2(8+2b) = -1 ,
b - 16 -4b = -1 , -3b = 15 , b = -5 代人(1) a +10 = 8 , a = -2
a = -2 , b = -5
2. 0.25(x+2y) = 0.6(3x+4y) -0.04y .......(1)
2x - y = x-3y / 3 + 10 ......(2)
由(1) 得 0.25x + 0.5y = 1.8x +2.4y -0.04y
-1.55 x = 1.86 y .....(3)
由(2) 得 6x - 3 y = x -3 y +30
5x = 30 , x = 6 代入第 3
1.86 y = -1.55*6
y = -5
x = 6 , y = -5
參考資料 我
This entry passed through the Full-Text RSS service — if this is your content and you're reading it on someone else's site, please read the FAQ at fivefilters.org/content-only/faq.php#publishers.